EFEKTIVITAS PERANGKAP YANG DIGUNAKAN DALAM KOLEKSI MAMALIA KECIL RODENSIA DAN EULIPOTYPHLA - Zulkurnia Irsaf; Annawaty Annawaty; Anang Setiawan Achmadi (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Ecological studies of small mammals often use several methods with various traps. Effective use of traps can increase the number of catches in this study. Small mammal samples were taken using the method of removal sampling for species diversity and set the traps using random purposive sampling method. In this case we use three types of traps, i.e. snap traps with roasted coconut bait smeared with peanut butter, pitfall traps with drift fence and rat snare with fruit as bait. Collection and installation of bait done at 07.00 WITA in the morning. From this study it is known that the use of traps falls very effectively in the study of small mammals, especially those living in terrestrial. This report provides information on common methods and effective traps are used in studying the diversity of small mammals.